RESULTS OF THEORETICAL AND PRACTICAL STUDY OF THE TECHNOLOGICAL PROCESS OF THE DEVELOPED HEAVY MIXTURE HOLDER (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
The article presents the theoretical study results on the effect of a softening long-pinned drum used in the holder of developed heavy mixtures. It analyzes the forces acting on cotton tufts when they strike the long-pinned drum after being transported through a pneumatic pipe. The motion of the cotton tufts and the efficiency of separating heavy mixtures from their composition are shown through equations and graphs. Specifically, considering the operating conditions of equipment used in cotton-cleaning enterprises and the pneumatic transport system—where the flow rate and air velocity at the inlet pipe are approximately 5 m³/s and 40 m/s, respectively—the speed of the transported cotton tufts ranges mainly between 18 and 25 m/s, depending on their size and weight